THE CORRELATION BETWEEN MEAN ARTERIAL PRESSURE (MAP) EXAMINATION AND THE INCIDENCE OF PREECLAMPSIA - Aisyah Sulistiawati; Rosalinna Rosalinna; Siti Yulaikah (Midwifery Department, UNS (Universitas Sebelas Maret) Surakarta, 2024)
Background : Preeclampsia is the second contributor to death after bleeding. Effort are made to detect the incidence of preeclampsia early, one of which uses the mean arterial pressure examination. Objective : To determine the correlation of mean arterial pressure (MAP) examination with the incidence of preeclampsia, determine the characteristics of pregnant women based on parity, age and MAP examination results for case and control group, analyze the correlation between MAP examination with the incidence of preeclampsia at  PKU Muhammadiyah Delanggu Hospital. Methods : The type of research used was quantitative  case control design and data collection using retrospective. The sampling technique was purposive sampling. The number of sampels in this study were 66 respondents with a ratio of 1:1 between cases and controls, for cases 33 respondents and for controls 33 respondents from medical record data at PKU Muhammadiyah Delanggu Hospital in 2022. Data analysis technique used non-parametric statistics chi square with a significance level of 0,05. Results : According to the results of statistical tests with the Fisher Exact Chi Square test with a confidence level of  95% (𝜎 = 5) and result of Exact. Sig. (2-Sided) is 0,000 (Exact. Sig (2-Sided) < 0,05). Conclusion :There is a statistically significant correlation between MAP examination and the occurrence of preeclampsia at PKU Muhammadiyah Delanggu Hospital.   Key word :Mean Arterial Pressure Examination, Preeclampsia